The Effectiveness of Javanese Philosophy-Based Interventions in Reducing Sociocomparative Attitudes (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This research, motivated by the socio-comparative phenomenon that occurs among children in orphanages, aims to evaluate the effectiveness of a gratitude intervention based on the Javanese philosophy "urip iku mung sawang sinawang" in abating socio-comparative attitudes and improving gratitude levels in orphans. The experimenters implemented a one-group pretest-posttest quantitative experimental design on 59 children from an orphanage in Surabaya, Indonesia. A total of 11 children participated in the intervention sessions from start to finish. Analysis of nonparametric data from the Wilcoxon rank test demonstrates that neither changes in socio-comparative attitudes (p=.247) nor gratitude levels (p=.264) could be considered statistically significant. Therefore, we have insufficient evidence to declare that the intervention was effective. Keyword: Sikap sosiokomparatif, kebersyukuran, desain eksperimen, falsafah jawa.